Economics of the Caspian Oil and Gas Wealth Companies, Governments, Policies - Kalyuzhnova, Yelena (Palgrave Macmillan UK, 2008)
This book explores the economic challenges involved in managing hydrocarbon wealth in the Caspian region, and looks at how to design an optimal energy policy. The book draws on the Author's experience in dealing with the governments of the region, and her knowledge of the role of major companies in the area
Keywords: Energy industries; Industrial organization; International economics; Economic policy; Economics; Environmental economics